The Determinants of Debt Ratio at Manufacturing Firms That Listed in Indonesia Stock Exchange - Farah Margaretha; Nafillah Fitrah (Universitas Trisakti, 2012)
This study purposed to acknowledge the determinants of debt ratio. Data research‘s drawn from 74 ftnns in manufacturing industry that listed in Indonesia Stock Exchange during period 2007 until 2009. Analysis method used is panel data regression with fixed effect model approach. Independent variables used are size. quick ratio, interest coverage ratio. growth. and investment opportunity. While dependent variable used in this study is debt ratio. Based on the result Fixed Effect Model. size. growth. and investment opportunity have no significantly effect to debtratio. While interest coverage ratio and quick ratio have significant effect on debt ratio. This study expected can give input to corporate managers to consider firms characteristic to determine optimal capital structure. Investors have to consider firms characteristic before investing. Investor better to invest in big company and has less debt because the risk is lower.Keywords : debt ratio. growth. interest coverage ratio. investment opportunity, quick ratio, size